(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
This study was conducted to see some of the toxic effects of pesticide carbaryl in Prussian carp fish Carassius auratus gibelio, where they were taken (40) fish from fingerlings Prussian carp obtained from the Diwaniyah River divided the fish randomly into four groups of 10 fish for each group, the first group was the control group , while the remaining totals presented to the following pesticide carbaryl concentrations (2.5, 5,7.5) mg / l, respectively for a period of 14 days. The results of the histological examination of the liver showed a cloudy swelling of hepatic cells with narrowing in the hepatocytes and a large expansion and thrombosis in the central vein. It also showed extensive necrosis with infiltration of lymphocytes and congestion in the central vein. The results of gills showed that there was extensive intra ventricular hemorrhage, with widely welling in large areas of gills. It was also noted the presence of large areas of necrosis with severe bleeding with infiltration of inflammatory cells. either spleen histopathological examination arises the presence of thrombus in the blood vessels clip in spleens fish carp Prussian also found necrosis in the splenic tissue with congestion in the blood vessels with the presence of macrophages while histological examination of kidney showed the presence of separation in some renal tubule with atrophy in some glomerular nephritis and the depletion in the blood tissue. And expansion in a vacuum Boman as well as the presence of necrosis widely in tubule T renal glomeruli.